DDX5 promotes proliferation and tumorigenesis of non‐small‐cell lung cancer cells by activating β‐catenin signaling pathway. Issue 10 (3rd September 2015) - Wang, Zhendong; Luo, Zhonghua; Zhou, Lin; Li, Xiaofei; Jiang, Tao; Fu, Enqing
Abstract : The DEAD‐box‐protein DDX5 is an ATP‐dependent RNA helicase that is frequently overexpressed in various cancers and acts as a transcriptional co‐activator of several transcription factors, including β‐catenin. DDX5 is reported to be involved in cancer progression by promoting cell proliferation and epithelial–mesenchymal transition. However, the clinical significance and biological role of DDX5 in non‐small‐cell lung cancer (NSCLC) remain largely unknown. In this study, we examined the expression of DDX5 in clinical NSCLC samples, investigated its role in regulating NSCLC cell proliferation and tumorigenesis, and explored the possible molecular mechanism. We found that DDX5 was significantly overexpressed in NSCLC tissues as compared with the matched normal adjacent tissues. In addition, overexpression of DDX5 was associated with advanced clinical stage, higher Ki67 index, and shorter overall survival in NSCLC patients. Upregulation of DDX5 promoted proliferation of NSCLC cells in vitro and growth of NSCLC xenografts in vivo, whereas downregulation of DDX5 showed the opposite effects. Furthermore, DDX5 directly interacted with β‐catenin, promoted its nuclear translocation, and co‐activated the expression of cyclin D1 and c‐Myc. β‐catenin silencing significantly abrogated DDX5‐induced cyclin D1 and c‐Myc expression and proliferation in NSCLC cells. Interestingly, DDX5 and cyclin D1 expression followed positive correlation in the same set of NSCLC samples. These findings indicated that DDX5 played an important role in the proliferation and tumorigenesis of NSCLC cells by activating the β‐catenin signaling pathway. Therefore, DDX5 may serve as a novel prognostic marker and potential therapeutic target in the treatment of NSCLC. Abstract : DDX5 played an important role in the proliferation and tumorigenesis of NSCLC cells via activating β‐catenin signaling pathway. DDX5 may be served as a novel prognostic marker and potential therapeutic target in the treatment of NSCLC.